Penerapan Model Polya Terhadp Hasil Belajar Soal Cerita Matematika Materi Perkalian dan Pembagian Siswa Kelas IV SDN 1 Tedunan Kabupaten Jepara - Yulanta Ilham Amalia; Muhajir Muhajir; Henry Januar Saputra (JANACITTA, 2020)
In learning Mathematics, conceptual understanding is a primary competency that the students must acquire, because through understanding the concept the students would understand what is being learned and are able to apply them thus they can pursue toward the next materials. However, in the reality of a learning process, the students have not yet understood the correctly. Therefore, researchers applied the Polya model. Thus, this study applies a learning model that can be applied and improves the learning outcomes of fourth grade students at SDN 1 Tedunan, Jepara Regency. This research method is quantitative research. In this research, the research is Des Experiment Desaign with the design of one group prettest-posttest. This study uses a pretest-posttest technique to improve problem solving skills in students. prestest is preliminary data obtained before students are treated using the polya model. Posttest is the final data obtained after students are treated using the polya model. This research was conducted on the fourth grade students at SDN 1 Tedunan Jepara Regency in the academic year 2019/2020 instruments used in this study were test sheets, lesson plans, validity tests, reliability tests. Level of pain and distinguishing power. Can decide the solution to the application of the model can be applied and improve problem solving solutions in fourth grade students at SDN 1 Teduana, Jepara Regency